2015
DOI: 10.14734/kjp.2015.26.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Edinburgh Postnatal Depression Scale for Postpartum Depression

Abstract: Purpose: Postpartum depression (PPD) is a common postnatal problem. PPD has a negative influence on maternal functioning and child development. We examined the result of Edinburgh Postnatal Depression Scale (EPDS) after delivery. Methods: Three hundred two postpartum mothers were enrolled in the study. The Korean version of EPDS was completed and scored at postpartum visits. Mothers whose score was 10 or more were classified as an EPDS positive for PPD. We reviewed their medical records and determined risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
5
0
6
Order By: Relevance
“…Korean women are reluctant to contact healthcare services for their depressive feelings because of the social stigma associated with mental illness (Klainin & Arthur, 2009). Continuous mental health management or services to assist women after birth for their wellbeing are often lacking (Ahn, Kang, Park & Choi, 2015).Furthermore, health care provider recognition of the importance of proper management of PPD remains low. Consequently, Korean women are left to search on their own for reliable health information and services for PPD (Kang, Kim, & Kim, 2012).…”
mentioning
confidence: 99%
“…Korean women are reluctant to contact healthcare services for their depressive feelings because of the social stigma associated with mental illness (Klainin & Arthur, 2009). Continuous mental health management or services to assist women after birth for their wellbeing are often lacking (Ahn, Kang, Park & Choi, 2015).Furthermore, health care provider recognition of the importance of proper management of PPD remains low. Consequently, Korean women are left to search on their own for reliable health information and services for PPD (Kang, Kim, & Kim, 2012).…”
mentioning
confidence: 99%
“…In Korea, there have been several validation studies of the EPDS in perinatal pregnant samples [5,7,10]. Previous studies in Korea [5,29,30] found that sensitivity was 77% and specificity was 87% using a cut -off score of 9/10. The present study used this cut-off score as the basis for classifying an individual as depressed or non-depressed.…”
Section: Edinburgh Postnatal Depression Scale (Epds)mentioning
confidence: 99%
“…The incidence of antenatal depression in Korea is 26-36% [3][4][5]. In addition, compared to the incidence of postpartum depression in Korea (10-28% [5,6]), the incidence of antenatal depression is very high.…”
Section: Introductionmentioning
confidence: 99%